2011
DOI: 10.1123/pes.23.1.151
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Squat and Countermovement Jump Tests in Children 6 to 8 Years of Age

Abstract: The aim of this study was to determine the reliability of the squat jump test (SJ) and countermovement jump test (CMJ), in fifty-six children (30 girls and 26 boys) with ages ranging from 6 to 8 years. Each subject performed two evaluation sessions (T1, T2) with seven days between tests. The results show that the CMJ test has a high intratrial reproducibility in T1 and T2 measured through intraclass correlation coefficient (ICC ≥ 0.95). The ICC for the SJ test had a high value (0.99) only in T1. The variabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 9 publications
0
25
1
2
Order By: Relevance
“…No familiarization sessions were conducted in previous studies (Juárez et al, 2008, 2010; Sousa et al, 2003). It is possible that the lack of familiarization sessions could increase the intra-subject variability (Acero et al, 2011), affecting the correlation analysis. In addition, the sample used in previous studies was very small, the soccer players were non-elite and under 15 years old (Juárez et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No familiarization sessions were conducted in previous studies (Juárez et al, 2008, 2010; Sousa et al, 2003). It is possible that the lack of familiarization sessions could increase the intra-subject variability (Acero et al, 2011), affecting the correlation analysis. In addition, the sample used in previous studies was very small, the soccer players were non-elite and under 15 years old (Juárez et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Four familiarization sessions were conducted where subjects practiced maximal kicking and jump tests, in order to minimize any learning or habituation effects. For vertical jumps we followed the procedure described by Acero et al (2011). To avoid inter-observer variability, the same experienced investigator tested all subjects.…”
Section: Methodsmentioning
confidence: 99%
“…At the end of the 6MWT, the 6MWD in meters (m) was noted and expressed as a percentage of the predicted local reference values (14): 6MWD (m)=4.63×height (cm) − 3.53×BM (kg)+10.42×age (years)+56.32. All tests have been shown to be valid and reproducible (2427). …”
Section: Population and Methodsmentioning
confidence: 98%
“…Prior to actual measurements, boys were familiarised with all the study tests to optimise their performance while minimising the learning effect (2427). Furthermore, they did not perform any strenuous physical activity (sport session at school, nor any other intense effort), 24 h before each testing period.…”
Section: Population and Methodsmentioning
confidence: 99%
“…Vertical jump tests are amongst the most common means of evaluating physical fitness in various populations (Buchheit, Spencer, & Ahmaidi, 2010;de Villarreal, Izquierdo, & Gonzalez-Badillo, 2011;Rodacki, Fowler, & Bennett, 2002;Taipale, Mikkola, Vesterinen, Nummela, & Häkkinen, 2013). Though principally used to evaluate leg power in sports such as basketball and football (Argus, Gill, Keogh, Hopkins, & Beaven, 2009;Duncan, Lyons, & Nevill, 2008;Hartman, Clark, Bemben, Kilgore, & Bemben, 2007), vertical jump tests have also been used to evaluate non-athletic populations (including children (Acero et al, 2011) and elderly people (Pereira et al, 2012)), particularly since vertical jump training has been reported to improve bonemineral density (Allison, Folland, Rennie, Summers, & Brooke-Wavell, 2013).…”
Section: Introductionmentioning
confidence: 99%